THE RELATIONSHIP OF STUDENTS' CREATIVITY LEVEL TO THE ABILITY TO WRITE THE NARRATIVE ESSAYS - Anjani Agusti; Aswadi Jaya; Mega Prasrihamni (Esteem Journal of English Education Study Programme, 2024)
Student creativity refers to the ability to create something new to provide knowledge in the learning process, such as writing narrative essays. This study aims to explain whether there is a relationship between the level of student creativity and the ability to write narrative essays of grade IV students of SDN 98 Palembang. This research uses correlation research method with quantitative approach. The results of this study indicate that the questionnaire of student creativity with a total score of 5 (8%) students in the moderately creative category, 29 (49%) students in the creative category, 25 (42%) students in the very creative category. The results of the narrative essay writing test show that 35 students scored above the average, which is 78. Many students have the ability to write narrative essays, namely 13 students are categorized as sufficient, 32 students are categorized as good, and 14 students are categorized as very good. Students are able to develop their creativity into a narrative essay. The results of the data show that there is a significant relationship between the level of student creativity and the ability to write narrative essays of grade IV students of State Elementary School 98 Palembang, which means accepting Ha and rejecting Ho. This research method is correlational, for further researchers can examine more deeply about the level of student creativity regarding writing skills.